2000
DOI: 10.1016/s0002-9297(07)62940-1
|View full text |Cite
|
Sign up to set email alerts
|

Mutations of the SCO1 Gene in Mitochondrial Cytochrome c Oxidase Deficiency with Neonatal-Onset Hepatic Failure and Encephalopathy

Abstract: Cytochrome c oxidase (COX) catalyzes both electron transfer from cytochrome c to molecular oxygen and the concomitant vectorial proton pumping across the inner mitochondrial membrane. Studying a large family with multiple cases of neonatal ketoacidotic comas and isolated COX deficiency, we have mapped the disease locus to chromosome 17p13.1, in a region encompassing two candidate genes involved in COX assembly-namely, SCO1 and COX10. Mutation screening revealed compound heterozygosity for SCO1 gene mutations i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
193
0
6

Year Published

2002
2002
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 207 publications
(203 citation statements)
references
References 32 publications
4
193
0
6
Order By: Relevance
“…Exceptions can be applied for instance to complex III-deficient patients harbouring mutations in the assembly factors BCS1L and TTC19, who showed normal complex I activity levels despite of a dramatic loss of fully-assembled complex III in different tissues (Fernandez-Vizarra et al, 2007;Ghezzi et al, 2011). Similarly, mutations in complex IV subunits or assembly factors often lead to isolated complex IV defects without complex I being affected (Tiranti et al, 1998;Zhu et al, 1998;Papadopoulou et al, 1999;Rahman et al, 1999;Valnot et al, 2000a;Valnot et al, 2000b;Antonicka et al, 2003;Massa et al, 2008). Such differences might be attributed to the nature of the mutation or the functional role of the OXPHOS mutated gene, and suggest that not all complexes III and IV structural genes are equally necessary to maintain complex I stability.…”
Section: Respiratory Chain Dysfunction: a Coupling Of Defective Assemmentioning
confidence: 99%
“…Exceptions can be applied for instance to complex III-deficient patients harbouring mutations in the assembly factors BCS1L and TTC19, who showed normal complex I activity levels despite of a dramatic loss of fully-assembled complex III in different tissues (Fernandez-Vizarra et al, 2007;Ghezzi et al, 2011). Similarly, mutations in complex IV subunits or assembly factors often lead to isolated complex IV defects without complex I being affected (Tiranti et al, 1998;Zhu et al, 1998;Papadopoulou et al, 1999;Rahman et al, 1999;Valnot et al, 2000a;Valnot et al, 2000b;Antonicka et al, 2003;Massa et al, 2008). Such differences might be attributed to the nature of the mutation or the functional role of the OXPHOS mutated gene, and suggest that not all complexes III and IV structural genes are equally necessary to maintain complex I stability.…”
Section: Respiratory Chain Dysfunction: a Coupling Of Defective Assemmentioning
confidence: 99%
“…Both encode mt proteins (Petruzzella et al, 1998;Paret et al, 1999), which are essential for mt function as shown by the recent detection of mutations associated with fatal COX deficiencies. Mutations in hSCO2 were reported in infants who suffered from a fatal disorder with hypertrophic cardiomyopathy as the predominant symptom (Papadopoulou et al, 1999;Jaksch et al, 2000Jaksch et al, , 2001a whereas the key symptoms of the infant patients carrying mutations in the hSCO1 gene were hepatic failure and ketoacidotic coma (Valnot et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to mutations in mitochondrial DNA-encoded COX genes 5,6 , mutations in nuclear DNA-encoded COX component genes and COX accessory factors cause COX deficiency [6][7][8] . For example, SURF1 is responsible for Leigh syndrome 9,10 , SCO1 for neonatal-onset hepatic failure and encephalopathy 11 , SCO2 for fatal infantile cardioencephalomyopathy 12 , and COX15 for fatal hypertrophic cardiomyopathy 13 . SCO1 and SCO2 are copper metallochaperones that are necessary for copper insertion into the catalytic core of COX assembly 14 .…”
mentioning
confidence: 99%